GIS-Based Spatial Risk Mapping of Aedes aegypti Larval Density and Dengue Transmission Risk in the Kassi-Kassi Community Health Center Area, Makassar City - Ashari Rasjid; Hamsir Ahmad; Rasman Rasman; Syamsuddin Suaebu; Budirman Budirman (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern in Makassar City, Indonesia. This study aimed to analyze the spatial distribution of Aedes aegypti larval density and its association with dengue transmission risk among children in the working area of the Kassi-Kassi Community Health Center. A quantitative cross-sectional design with a geographic information system approach was used. A total of households were selected using proportional simple random sampling. Data were collected through field observations, household surveys, and secondary data from health institutions. The results showed that temperature ranged from 25.3°C to 27.3°C, humidity from 70% to 89%, and rainfall from 45 mm to 463 mm. Larval density was classified into low-risk (0–4), medium-risk (5–9), and high-risk (10–15) categories, while larvae-positive houses ranged from 87.5% to 100%. Spatial analysis using showed that high-risk areas were concentrated in densely populated settlements with poor drainage and uncovered water storage containers. The association between larval density and dengue incidence was indicated by [insert correlation/index value; p-value]. This study was limited by its cross-sectional design, single study area, and incomplete ability to establish causal relationships. The findings support targeted dengue prevention through Mosquito Nest Eradication, 3M Plus education, and routine larval monitoring.